(3eONd Edi Yde GdELJeGY GdSjGSj (B/s - (3LGfOQhhchQahGRjjg,Thejdjg s; (3GdZRGd(B,(3ESeGYjds ((3dHfGf (B:s (3GdeDSSI GdLGeYjI ddOQGSGJ h GdfTQ h GdJhRjY ,s, 1988)
(3eaghe Yde GdELJeGY GdSjGSj (B-(3eaghe GddGSjGSjh eYGfjg(B-(3GdSdWI h GdeLJeY aj GdOhdI GdQGSeGdjI GdeJbOeI(B-(3GdSdWI h GdeLeJY ajGdOhd GdETJQGcjI (B-(3GdJfGbVGJ GdSjGSjI Ydi GdUYjO GdOhdjs
Keywords: (3Yde GdELJeGYs; (3Yde GdELJeGY GdSjGSjs